9 Out of 10 Patients Participate in Sports after Talar Osteoperiostic Grafting from the Iliac Crest for Large Osteochondral Lesions of the Talus - Jari Dahmen MD; Quinten Rikken MD; Sjoerd Stufkens MD, PhD; Gino M M.M.J. Kerkhoffs MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle Introduction/Purpose: Osteochondral lesions of the talus (OLT) are often caused by sports. The Talar OsteoPeriostic grafting from the Iliac Crest (TOPIC) is an autologous press-fit bone grafting technique for large (cystic) primary- and non-primary OLT. The purpose of this study was to prospectively evaluate sport outcomes after the TOPIC surgery. The purpose of this study was to prospectively evaluate sports outcomes for patients with OLT who were treated with the TOPIC procedure. Methods: 61 patients who underwent the TOPIC procedure for a symptomatic OLT were prospectively included up-to 24 months follow-up. Using digital questionnaires, an in-depth telephone interview, and electronic patient files, the return to any level of sport (primary outcome), the return to preoperative level of sport, the return to preinjury level of sport, the return to performance, the participation in improved preoperative level of sport and participation in desired level of sport rates were determined 1- and 2-years after TOPIC. On top of that the Ankle Activity Scale (AAS), Numeric Rating Scale (NRS) for pain while running preoperatively, 1- and 2-years after TOPIC were assessed. Lastly complication and reoperation types and rates were presente Results: 2 years after TOPIC surgery, 98% of patients returned to any level of sport. Of the 61 participants, 90% participated in an improved level of sports compared to pre-operatively, 59% returned to their preinjury level of sports and 3% returned to perform on a higher level of sports than preinjury. The AAS increased significantly from 2 to 5 out of 10 (p < 0.01) both 5 points both 1- and 2-years post-TOPIC. The NRS for pain during running improved from 9 to 5 out of 10 (p < 0.01) 5 points both 1- and 2-years post-TOPIC. Any complication occurred in 3% of cases and in 31% of cases a reoperation was conducted, primarily due to hardware removal. Conclusion: The TOPIC procedure for large OLT results in high return to sport and participation in sport rates 1- and 2-years postoperatively making it a suitable treatment option for the athletic population suffering from OLT.